A transmembrane protein family gene signature for overall survival prediction in osteosarcoma - Du, Yuehui; Zeng, Xiaohui; Yu, Weiwei; Xie, Wei (Frontiers in Genetics, 2022)
The transmembrane (TMEM) protein family is constituted by a large number of proteins that span the lipid bilayer. Dysregulation of TMEMs protein genes are widely occurs and associated with clinical outcome of patients in multiple tumors. Nonetheless, the significance of TMEM genes in the prognosis prediction of patients with osteosarcoma remains largely unclear. Here, we comprehensively analyzed TMEM protein family genes in osteosarcoma using public resources and bioinformatic methods. Prognosis-related TMEM protein family genes were identified by the univariate Cox regression analysis and were utilized to construct a six TMEM protein family gene (TMEM120B, TMEM147, TMEM9B, TMEM8A, TMEM59, and TMEM39B) based signature in osteosarcoma. The prognostic signature stratified patients into high- and low-risk groups, and validation in the internal and external cohorts confirmed the risk stratification ability of the signature. Functionally enrichment analyses of differentially expressed genes between high- and low-risk groups connected immunity with the prognostic signature. Moreover, we found that M2 and M0 macrophages were the most abundant infiltrated immune cell types in the immune microenvironment and samples of high-risk group had decreased M2 Macrophages proportion. ssGSEA analysis revealed that the scores of Neutrophils and Treg were markedly lower in high-risk group than these in low-risk group in TCGA and GSE16091 cohorts. As for the related immune functions, APC co-inhibition and cytolytic activity exhibited fewer active levels in high-risk group than that in low-risk group in both cohorts. Of the six TMEM genes, the expression of TMEM9B was lower in high-risk group than that in low-risk group and was positively associated with the overall survival of osteosarcoma patients. In conclusion, our TMEM protein family gene-based signature is a novel and clinically useful prognostic biomarker for osteosarcoma patients, and TMEM9B might be a potential therapeutic target in osteosarcoma.